2011
DOI: 10.1038/tpj.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase genotypes and haplotypes modify the responses to sildenafil in patients with erectile dysfunction

Abstract: Erectile dysfunction (ED) is usually treated with sildenafil. Although genetic polymorphisms in the endothelial nitric oxide synthase (eNOS) gene may impair endogenous NO formation, there is little information about how eNOS polymorphisms and haplotypes affect the responses to sildenafil. We studied 118 patients; 63 patients had ED secondary to radical prostatectomy (PED) and 55 had organic, clinical ED. eNOS genotypes for three eNOS polymorphisms (T(-786)C, rs2070744; a variable number of tandem repeats (VNTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…A key effector in the NO–cGMP pathway is endothelial NO synthase (eNOS). In two separate studies, the 4a variable number tandem repeat in intron 4 of NOS3 (the gene that encodes eNOS) was associated with better ED response to sildenafil [121,122]. A separate group replicated this variable number tandem repeat association and also found an association between C allele in T-786C and good response to sildenafil [122].…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key effector in the NO–cGMP pathway is endothelial NO synthase (eNOS). In two separate studies, the 4a variable number tandem repeat in intron 4 of NOS3 (the gene that encodes eNOS) was associated with better ED response to sildenafil [121,122]. A separate group replicated this variable number tandem repeat association and also found an association between C allele in T-786C and good response to sildenafil [122].…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
“…In two separate studies, the 4a variable number tandem repeat in intron 4 of NOS3 (the gene that encodes eNOS) was associated with better ED response to sildenafil [121,122]. A separate group replicated this variable number tandem repeat association and also found an association between C allele in T-786C and good response to sildenafil [122]. A retrospective study suggests that variation in GNB3 , a gene that encodes a key component of intracellular signal transduction in G-protein-coupled receptors, affects sildenafil response in ED [123].…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
“…Limited and inconsistent data from small to moderate size studies have suggested that genetic variants related to a variety of biological pathways could influence sildenafil's hemodynamic effects in patients with pulmonary hypertension or its efficacy in treating erectile dysfunction. [4][5][6][7][8][9] Considering that a majority of the markers judged to be clinically useful by the National Institutes of Health's Clinical PGx Implementation Consortium are absorption, distribution, metabolism and elimination (ADME) genes, 10 it is surprising that few studies have focused on variants of genes which could modulate sildenafil concentrations and dosing requirements. In particular, given that sildenafil is extensively metabolized in the liver by the cytochrome P450 3A (CYP3A) isoenzymes (major metabolizing route; 79%) and CYP2C9 (20%), [11][12][13] genetic variants coding for these isoenzymes would biologically appear to be likely genetic modulators of the effects of sildenafil.…”
Section: Introductionmentioning
confidence: 99%
“…Various eNOS gene polymorphisms have been described (10), such as insertions/deletions, microsatellites, single nucleotide polymorphisms (SNPs), and variable number of tandem repeats (VNTRs). NO signaling can be modulated by different drugs, and their effect may be influenced by eNOS gene polymorphism (12)(13)(14)(15)(16)(17)(18). Despite being constitutively expressed, eNOS is regulated by many stimuli at transcriptional, posttranscriptional and posttranslational level (19).…”
mentioning
confidence: 99%